Ageing Poorly? Accounting for the Decline in Earnings Inequality in Brazil, 1995-2012 - Francisco H. G. Ferreira; Sergio Firpo; Julián Messina (Institute of Labor Economics (IZA), 2017)
The Gini coefficient of labor earnings in Brazil fell by nearly a fifth between 1995 and 2012, from 0.50 to 0.41. The decline in earnings inequality was even larger by other measures, with the 90-10 percentile ratio falling by almost 40 percent. Although the conventional explanation of a falling education premium did play a role, an RIF regression-based decomposition analysis suggests that the decline in returns to potential experience was the main factor behind lower wage disparities during the period. Substantial reductions in the gender, race, informality and urban-rural wage gaps, conditional on human capital and institutional variables, also contributed to the decline. Although rising minimum wages were equalizing during 2003-2012, they had the opposite effects during 1995-2003, because of declining compliance. Over the entire period, the direct effect of minimum wages on inequality was muted.
Keywords: D31; J31; 330; earnings inequality; Brazil; RIF regressions